Bone Marrow Microenvironment in Acute Myleoid Leukemia - Chandran, Priya (Université d'Ottawa / University of Ottawa, 2013)
Acute myeloid leukemia (AML) often remains refractory to current chemotherapy and transplantation approaches despite many advances in our understanding of mechanisms in leukemogenesis. The bone marrow “niche” or microenvironment, however, may be permissive to leukemia development and studying interactions between the microenvironment and leukemia cells may provide new insight for therapeutic advances. Mesenchymal stem cells (MSCs) are central to the development and maintenance of the bone marrow niche and have been shown to have important functional alterations derived from patients with different hematological disorders. The extent to which MSCs derived from AML patients are altered remains unclear. The aim of this study was to detect changes occurring in MSCs obtained from human bone marrow in patients with AML by comparing their function and gene expression pattern with normal age-matched controls. MSCs expanded from patients diagnosed with acute leukemia were observed to have heterogeneous morphological characteristics compared to the healthy controls. Immunohistochemistry and flow data confirmed the typical cell surface immunophenotype of CD90+ CD105+ CD73+ CD34- CD45-, although MSCs from two patients with AML revealed reduced surface expression of CD105 and CD90 antigens respectively. Differentiation assays demonstrated the potential of MSCs from AML patients and healthy donors to differentiate into bone, fat and cartilage. However, the ability of MSCs from AML samples to support hematopoietic function of CD34+ progenitors was found to be impaired while the key hematopoietic genes were found to be differentially expressed on AML-MSCs compared to nMSCs. These studies indicate that there exist differences in the biologic profile of MSCs from AML patients compared to MSCs derived from healthy donors. The results described in the thesis provide a formulation for additional studies that may allow us to identify new targets for improved treatment of AML.
Keywords: Acute Myeloid Leukemia; Bone Marrow niche; Mesenchymal Stromal cells